2022
DOI: 10.1158/1538-7445.am2022-lb111
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB111: Comparison of the predictive and prognostic significance of circulating tumor DNA in patients with high risk HER2-negative breast cancer receiving neoadjuvant chemotherapy

Abstract: Background: We compared the predictive and prognostic value of ctDNA dynamics in high-risk hormone receptor-positive/HER2-negative (HR+/HER2-) and triple negative breast cancer (TNBC) receiving neoadjuvant chemotherapy (NAC) enrolled in the I-SPY 2 trial (NCT01042379). To our knowledge, this is the largest ctDNA study in breast cancer in the neoadjuvant setting. Methods: Blood samples were collected at pre-treatment (T0), during treatment (T1 at 3 weeks, and T2 at 12 weeks) and after NAC (T3 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Had IGFBP7 been included in the initial assessment of predictive biomarkers in I-SPY2, it would have identified the distinct subgroup where ganitumab showed benefit. Our findings add to the list of important studies 8,[10][11][12][13] where the I-SPY2 trial detected activity of novel agents 7,8,12,13 , even if the benefit is shown to be confined to a biomarker-defined subset of patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Had IGFBP7 been included in the initial assessment of predictive biomarkers in I-SPY2, it would have identified the distinct subgroup where ganitumab showed benefit. Our findings add to the list of important studies 8,[10][11][12][13] where the I-SPY2 trial detected activity of novel agents 7,8,12,13 , even if the benefit is shown to be confined to a biomarker-defined subset of patients.…”
Section: Discussionmentioning
confidence: 63%
“…Further, eleven putative IGF-1R signaling axis biomarkers were tested, but none were predictive of ganitumab benefit 5 . I-SPY2 has been able to identify treatment predictive biomarkers for emerging treatments due to its unique design [6][7][8][9] , and to evaluate efficacy of new treatments [10][11][12][13] . To further this goal, the I-SPY2-990 Data Resource has been made publicly available 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study with longitudinal ctDNA monitoring, confirmed the strong prognostic significance of ctDNA persistence in patients with TNBC (hazard ratio: 27.6, 5.9-128.8) [65]. Consistently, the investigators of the I-SPY 2 adaptive, multiarm clinical trial reported retrospective data on MRD in patients treated with neoadjuvant therapy, and not experiencing pCR [63,66]. In a multivariate model, they showed that pCR has no independent prognostic significance, when ctDNA is included as a variable: the only independent factor associated with disease recurrence was the persistence of ctDNA postsurgically (hazard ratio: 14.9, 2.66-83.11) [63].…”
Section: Approach 3: Treatment Intensification Based On Postsurgical ...mentioning
confidence: 65%
“…The proportion of patients with residual disease and detectable ctDNA was 14% in this study, suggesting that not all patients with residual disease are at highest risk of recurrence but perhaps a smaller subset. Of note, ctDNA was not detectable in all patients with pCR [63,66]. The risk of distant relapse was similar for patients achieving pCR and patients with residual disease but negative postsurgical ctDNA (hazard ratio: 1.4, 0.15-13.5).…”
Section: Approach 3: Treatment Intensification Based On Postsurgical ...mentioning
confidence: 91%
“…It should also be noted that the blood-based biomarkers tested only included T cell counts and ratios of cell counts. Liquid biopsy-based biomarkers such as circulating tumor cells and circulating tumor DNA have potential for predicting outcomes and recurrence risk in early-stage breast cancer 58, 59 . These biomarkers could also predict immunotherapy efficacy in metastatic cancer 17 , though this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%